HISTOPATHOLOGICAL AND MOLECULAR CHARACTERISTICS OF COLORECTAL CANCER – REVIEW OF THE SIGNIFICANCE OF THE EPITHELIAL-MESENHYMAL TRANSITION - Đikić Rom, Aleksandra; Barisic, Goran (Medicinski podmladak, 2024)
Colorectal cancer (CRC) is the third most frequently diagnosed cancer and the second most common cause of death among malignant neoplasms, including both sexes. The most important prognostic and predictive factors for CRC are the histological type and grade of the tumor, TNM stage of the tumor disease, lympho-vascular and perineural infiltration, tumor budding and residual status. The molecular classification of CRC is based on its genetic characteristics, cellular specifications, cancer microenvironment and immunological characteristics, and is of great practical importance, as individual subtypes differ in their clinical course and respond differently to chemotherapeutic and biological treatment. Epithelial-mesenchymal transition (EMT) is a transdifferentiation process in which epithelial cells acquire properties that are characteristic of mesenchymal cells. During neoplastic progression, cancer cells acquire genetic and epigenetic features that affect oncogenic and tumor suppressor genes, which ultimately results in the activation of the type III EMT programme, giving them the potential to invade and metastasize, contributing to the stemness of cancer cells, their resistance to drugs and immune response avoidance. Changes made in cells, during EMT, can be reversible upon arrival at a suitable location for colonization, by a process opposite to EMT, called mesenchymal-epithelial transition (MET), during which cells regain characteristics of the epithelial phenotype. In most human cancer types, a complete shift from an epithelial to a mesenchymal phenotype during EMT is rarely encountered, but most cancers show partial EMT. Cells undergoing partial EMT are difficult to identify, due to their phenotypic heterogeneity and variable expression of EMT markers. It is necessary to find new biomarkers of EMT, especiallypartial EMT, as well as a better understanding of the relationship between EMT and resistance to therapy, in order to develop new therapeutic approaches for CRC.